2022
DOI: 10.1590/1519-6984.232805
|View full text |Cite
|
Sign up to set email alerts
|

Community structure of benthic invertebrates in the Allipén River basin, North Patagonia, Araucania region (38º S, Chile)

Abstract: One of the biological indicators most used to determine the health of a fluvial ecosystem are the benthic macroinvertebrates. The presence of recurrent species in a wide gradient of latitudes, dominates the biogeographic pattern of the benthic macroinvertebrates in Chilean fresh waters, nevertheless the knowledge on the communitarian ecology of these in the Chilean rivers continues to be scarce. Null models became a powerful statistical tool for describing the ecological mechanisms that drive the structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…(2021), who found associations between groups reported and environmental parameters for Chilean North Patagonian rivers. In this scenario, the macroinvertebrate assemblage fauna in the studied river is similar to observations for central and southern Chilean rivers (35-40º S;Fierro et al, 2015;Figueroa et al, 2003Figueroa et al, , 2007Figueroa et al, , 2013Vega et al, 2020;Barile et al, 2021), where it was found marked differences in community structure in function to river zone, where it is possible found that in high zones there are shredders (Ephemeroptera, Plecoptera) that requires water quality with high oxygen content and low dissolved organic matter contents and nutrient concentration (Moya et al, 2009;Oyanedel et al, 2008;Miserendino et al, 2018;De los Ríos-Escalante et al, 2020;Solis-Lufi et al, 2021).…”
Section: Tablesupporting
confidence: 86%
“…(2021), who found associations between groups reported and environmental parameters for Chilean North Patagonian rivers. In this scenario, the macroinvertebrate assemblage fauna in the studied river is similar to observations for central and southern Chilean rivers (35-40º S;Fierro et al, 2015;Figueroa et al, 2003Figueroa et al, , 2007Figueroa et al, , 2013Vega et al, 2020;Barile et al, 2021), where it was found marked differences in community structure in function to river zone, where it is possible found that in high zones there are shredders (Ephemeroptera, Plecoptera) that requires water quality with high oxygen content and low dissolved organic matter contents and nutrient concentration (Moya et al, 2009;Oyanedel et al, 2008;Miserendino et al, 2018;De los Ríos-Escalante et al, 2020;Solis-Lufi et al, 2021).…”
Section: Tablesupporting
confidence: 86%